2020
DOI: 10.1177/1753193420939379
|View full text |Cite
|
Sign up to set email alerts
|

An ulnar parametacarpal perforator flap for volar digital soft tissue reconstruction

Abstract: We present outcomes of using a perforator-based ulnar parametacarpal flap in 25 patients for digital pulp defects. These included 17 free transfers to the thumb, index, middle and ring fingers and eight reverse pedicled transfers to the little fingers. This flap includes a dorsal sensory branch of the ulnar nerve, which was sutured to the digital nerve in all transfers. Each flap had one to three reliable perforators (mean 0.44 mm diameter) to the ulnar parametacarpal region and contained at least one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…We never favoured nor used small free flaps for the digit-tip defect and consider it unnecessary. Adani (2020Adani ( , 2021 expressed this concern to a small free flap (Usami et al, 2020), and we agree. Complex surgery is not justified if simpler methods exist, and sensation rather than slightly shortening the bone is more important (Lam and Jordan, 2019;Tang, 2019).…”
Section: Dear Editormentioning
confidence: 66%
“…We never favoured nor used small free flaps for the digit-tip defect and consider it unnecessary. Adani (2020Adani ( , 2021 expressed this concern to a small free flap (Usami et al, 2020), and we agree. Complex surgery is not justified if simpler methods exist, and sensation rather than slightly shortening the bone is more important (Lam and Jordan, 2019;Tang, 2019).…”
Section: Dear Editormentioning
confidence: 66%
“…In addition, numbness and sensory loss of the dorsal surface of the little finger improved over 1 year in many cases, resulting in a highly satisfactory rate (Usami et al, 2020). Previously, the UMP flap was indicated for small to middle‐sized defect (Usami et al, 2020); however, this paper demonstrated that the dorsal extended UPM flap design could enhance flap indication, especially suitable for the reconstruction of total pulp defects of the digit which is difficult to cover with conventional Hemi‐pulp flap. This flap offers functional and esthetic tissue similar to digital pulp and a long pedicle with high flexibility for reconstructing the digital tip.…”
Section: Discussionmentioning
confidence: 99%
“…Yamamoto expanded the indications for a free hypothenar flap by using a local flap from the ulnar side of the hand (Yamamoto et al, 2022). Similarly, the width of the UMP flap for direct closure of the donor site is limited; however, depending on the case, it is sometimes difficult for direct closure to exceed 2 cm (Usami et al, 2020). To increase the flap width, we designed a dorsal V‐Y sliding flap containing a fourth dorsal metacarpal artery perforator for direct closure of the donor site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This flap is different because it is a completely reversed flow flap, where they compromise the ulnar digital artery of the little finger, and so it augments its blood supply. 16 Usami et al 17 reported the application of perforator-based free or reverse pedicled ulnar parametacarpal artery flaps on series of 25 patients with 17 free transfers to the thumb, index, middle and ring fingers, and eight reverse pedicled transfers to the little fingers. They used these flaps based on the palmar digital system.…”
Section: Discussionmentioning
confidence: 99%